Electroencephalogram Monitoring in Critical Care - Rubinos, Clio; Alkhachroum, Ayham; Der-Nigoghossian, Caroline; Claassen, Jan (Seminars in Neurology, 2020)
Seizures are common in critically ill patients. Electroencephalogram (EEG) is a tool that enables clinicians to provide continuous brain monitoring and to guide treatment decisions—brain telemetry. EEG monitoring has particular utility in the intensive care unit as most seizures in this setting are nonconvulsive. Despite the increased use of EEG monitoring in the critical care unit, it remains underutilized. In this review, we summarize the utility of EEG and different EEG modalities to monitor patients in the critical care setting.
Keywords: Electroencephalogram; intensive care unit; seizures; status epilepticus